(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
Cattle grazing on natural grasses and improved, and the use of feed protein resources from the contribution of trees and shrubs, is as old as his own existence. However, modern livestock production systems resulted to the use of intensive technologies, based on other protein-energy resources that could replace the grass-based diets or the use of cut and carry systems of forage over large areas of monoculture. In this context, much of the production of beef in Cuba took place in stables, with technologies of total or partial confinement, where sugar cane molasses (in combination with urea in different proportions) and protein supplements were part of the diet of the animals, while the use of limited grazing forage and passed the background. For improved milk production dairy herds from the racial point of view, with the introduction of Holstein blood from European countries and Canada as well as general infrastructure through the development of production units with specific facilities and areas of grassland 40-110 and forage grass has covered. However, to achieve expression of the dairy potential of the animals was necessary to supplement with imported concentrates and fertilize areas of grasses and forages. These technologies showed great unsustainable due to its aggression against the environment and dependence on external inputs, which is particularly important in tropical areas where countries are located in poorer economies. In this context, the renewal and introduction of appropriate grasses, adapted to local soil and climatic conditions, together with the strategic incorporation of tree and shrub plants in the grazing areas is an alternative technology that would improve cattle production, decreasing negative impact on the ecosystems in which it develops. This could be an economically viable solution, which causes damage to the environment and is socially accepted, whose short-term benefits are manifest in a steady increase in animal production.